If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4x = 1 Combine like terms: 2x + -4x = -2x -2x = 1 Solving -2x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = -0.5 Simplifying x = -0.5
| 6s^2-13s+2= | | 5a^2+13a-6= | | 10x+3y=121 | | 6x-1=3x | | 4y-8x=12 | | (4x+5)(2x-3)= | | -3x^2-13x-4= | | 116-6=2x+20 | | 7b^2-17ab+6a^2= | | 4x=2x-10 | | 3r^2-5rs+2s^2= | | 20+23a-21a^2= | | x=2.5(1-x) | | 4y+12+3y-3=23 | | 125-4x=41x+15 | | (n-4)*2=10 | | 5a+7=32 | | 2x+17=10x-37 | | 7x-0.05-2x=3.15 | | -16n+12-14n=-8 | | 12t+35-2t=20 | | 12+35-2t=20 | | 4a-3=2 | | 11x+2=-20 | | 6x^2-6x-11655=0 | | 5(1+x)=2(x-5) | | 14-3*(3-3x)=50 | | 5x-(-15-4x)+16=-14 | | 8x+(-7-5x)+25=-9 | | 3-8*(2+4x)=19 | | 3-8*(2+5x)=19 | | 5x-(-9+2x)+16=4 |